Lupus Enteritis as an Initial Presentation of Systemic Lupus Erythematosus - Sisira Sran; Manpreet Sran; Narmisha Patel; Prachi Anand (Case Reports in Gastrointestinal Medicine)
Systemic lupus erythematosus (SLE) is an autoimmune disorder which can affect multiple organs and clinical presentation is often a myriad of symptoms; therefore, the index of suspicion should rise when evaluating patients with multiorgan symptomatology. Lupus enteritis is a distinct subset of SLE, defined as either vasculitis or inflammation of the small bowel, with supportive image and/or biopsy findings. The clinical picture of lupus enteritis is often nonspecific, with mild to severe abdominal pain, diarrhea, and vomiting being the cardinal manifestations. Although considered a form of visceral or serosal vasculitis, lupus enteritis is seldom confirmed on histology, making computerized tomography (CT) the gold standard for diagnosis. Lupus enteritis is generally steroid-responsive, and the route of administration is based on clinical status and organ involvement, with preference for intravenous (IV) route in flares with significant tissue edema. The following case describes a young woman presenting with lupus enteritis and lupus panniculitis as an initial manifestation of SLE, the utilization of abdominal CT in diagnosis, and current treatment protocols used for lupus enteritis.